ETIKA ADMINISTRASI PUBLIK - Holilah, Holilah (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
The deviation of administrative ethics are still common. Many factors that cause it both external and internal factors. Therefore, this study seeks to examine the ethical values and violations that occur in public administration. The results showed: first, the ethical values were the value of the efficiency of public administration, the value of private property with the property distinguishes office, impersonal value, value merytal system, the value of responsibility, the value of accounttability, the value of responsiveness. Second, the violations that occurred in public administration ethics were dishonesty, bad behavior, conflict of interest, violation of laws, unfair treatment toward subordinates, violation of procedures, inefficiency, whitewashing, and failure to take the initiative.